If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 12 = 68 + 6x Reorder the terms: 12 + 2x = 68 + 6x Solving 12 + 2x = 68 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 12 + 2x + -6x = 68 + 6x + -6x Combine like terms: 2x + -6x = -4x 12 + -4x = 68 + 6x + -6x Combine like terms: 6x + -6x = 0 12 + -4x = 68 + 0 12 + -4x = 68 Add '-12' to each side of the equation. 12 + -12 + -4x = 68 + -12 Combine like terms: 12 + -12 = 0 0 + -4x = 68 + -12 -4x = 68 + -12 Combine like terms: 68 + -12 = 56 -4x = 56 Divide each side by '-4'. x = -14 Simplifying x = -14
| 5x+2y^2=3 | | (h-78)/9(1)+(-13)+50-(78*.25)=-20 | | 4(2x-1)=-28 | | 4(x-8)=0 | | 22=t | | 8+1.25=16.75 | | 3x+38=16+x | | 184+2h=986 | | x+3x-1+x+15= | | 3x^2-6x+11000=0 | | 4x(x)=49 | | 2x^6*x-95=0 | | 0.2p-10= | | 6-4x=x+7(x+8) | | 144=16t | | 28(p+30)=3,108 | | 8.32+7.76-10.09= | | 3,108=28(p+30) | | x+(3x+4)=112 | | 6(2x-3)=24 | | X+(x-21)=157 | | 2x+12+7x-1=x | | 2(3x+3)=11x+3-5x+3 | | z/(-1)=9 | | -8+x=46 | | X+X-21=157 | | 6.8/(-4)= | | 2x+11x=52+x | | x-(-5)=34 | | 9x+15=5x+1 | | 4*(-4.3)*-2= | | X^2-15x-11000=0 |